A comparative assessment of Lactiplantibacillus plantarum isolated from chicken and humans as candidates for probiotics - JESSICA SUNARDI; EMILY TANIA PURNAMA; MARCELIA SUGATA; HANS VICTOR; TAN TJIE JAN; JUANDY JO (Society for Indonesian Biodiversity, 2023)
Abstract. Sunardi J, Purnama ET, Sugata M, Victor H, Jan TT, Jo J. 2023. A comparative assessment of Lactiplantibacillus plantarum isolated from chicken and humans as candidates for probiotics. Biodiversitas 24: 5198-5206. Lactiplantibacillus plantarum is commonly analyzed as a potential probiotic. We hereby investigated two strains isolated from chicken crop (Lpb. plantarum F75) and human breast milk (Lpb. plantarum SU-KC1a). Ability to withstand osmotic stress (1.5%, 2.5% or 3.5% of NaCl) and phenol compounds (0.2% or 0.5%), ability to survive gastric juices for a maximum of 120 minutes and bile salt for a maximum 3 hours, as well as susceptibility to 25 antibiotic discs, were compared between both strains. Whole genomes of both strains were sequenced and analyzed in silico to determine the availability of antibiotic-resistance genes as well as the presence of mobile genetic elements and plasmid. Both strains were sensitive to increased concentrations of NaCl and phenol as well as to prolonged exposure to gastric juices. In contrast, both strains could withstand a prolonged exposure of 0.3% of bile salt. Both isolates had similar genome sizes and were susceptible to many tested antibiotics. The detected resistance genes were observed within the chromosomal genomes but no mobile genetic element nor plasmid was found. In conclusion, both strains of Lpb. plantarum displayed several characteristics of beneficial bacteria and could be used as probiotic candidates for poultry and human beings, respectively.